Albumin treatment of critical conditions on the example of pre-eclampsia - O. M. Klygunenko; O. V. Kravets; O. O. Zozulya; O. O. Marzan; Yu. O. Ploshchenko; V. A. Sedinkin; D. M. Stanin (Zaporožskij Medicinskij Žurnal, 2025)
Despite the well-documented physicochemical and pharmacodynamic properties of albumin solutions and the availability of clinical guidelines for their use in critical conditions, several aspects of their application, particularly in the context of pre-eclampsia, remain a matter of clinical debate.